Filamentous fungi for sustainable remediation of pharmaceutical compounds, heavy metal and oil hydrocarbons - Ghosh, Soumya; Rusyn, Iryna; Dmytruk, Olena V.; Dmytruk, Kostyantyn V.; Onyeaka, Helen; Gryzenhout, Marieka; Gafforov, Yusufjon (Frontiers in Bioengineering and Biotechnology, 2023)
This review presents a comprehensive summary of the latest research in the field of bioremediation with filamentous fungi. The main focus is on the issue of recent progress in bioremediation of pharmaceutical compounds, heavy metal treatment and oil hydrocarbons biomycoremediation that are usually insufficiently represented in other reviews. It encompasses a variety of cellular mechanisms involved in bioremediation used by filamentous fungi, including bio-adsorption, bio-surfactant production, bio-mineralization, bio-precipitation, as well as extracellular and intracellular enzymatic processes. Processes for wastewater treatment accomplished through physical, biological, and chemical processes are briefly described. The species diversity of filamentous fungi used in pollutant removal, including widely studied species of Aspergillus, Penicillium, Fusarium, Verticillium, Phanerochaete and other species of Basidiomycota and Zygomycota are summarized. The removal efficiency of filamentous fungi and time of elimination of a wide variety of pollutant compounds and their easy handling make them excellent tools for the bioremediation of emerging contaminants. Various types of beneficial byproducts made by filamentous fungi, such as raw material for feed and food production, chitosan, ethanol, lignocellulolytic enzymes, organic acids, as well as nanoparticles, are discussed. Finally, challenges faced, future prospects, and how innovative technologies can be used to further exploit and enhance the abilities of fungi in wastewater remediation, are mentioned.